2021
DOI: 10.1097/jcma.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular aortic repair is a cost-effective option for in-hospital patients with abdominal aortic aneurysm

Abstract: Background: To investigate the cost-effectiveness of endovascular aortic repair (EVAR) versus open aortic repair (OAR) for abdominal aortic aneurysm (AAA) using incremental costs per decreased in-hospital mortality rate gained through our patients’ cohort. Methods: Medical records and healthcare costs of patients with AAA hospitalized between 2010 and 2015 were extracted from the National Health Insurance Research Database (NHIRD) of Taiwan. Multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The major material cost was for endografts with the special materials fee for EVAR accounted for 60 to 75% of the total medical expenses, which indicated that the special materials fee for the surgery impacted the overall medical expenses regardless of the preoperative condition. 17 This study showed the total medical expenses per patient who received EVAR is TWD 605,573, when it is converted to rupiah will cost approximately 300 million Indonesian rupiah. According to this data, the amount of medical expenses has the potential to become an issue for the patient and the team of doctors in achieving optimal treatment, with the coverage from the National Health Insurance (Jaminan Kesehatan Nasional [JKN]) hopefully will reduce the economic burden on certain health issues, especially medical expenses in AAA cases that require an EVAR procedure.…”
Section: Discussionmentioning
confidence: 92%
“…The major material cost was for endografts with the special materials fee for EVAR accounted for 60 to 75% of the total medical expenses, which indicated that the special materials fee for the surgery impacted the overall medical expenses regardless of the preoperative condition. 17 This study showed the total medical expenses per patient who received EVAR is TWD 605,573, when it is converted to rupiah will cost approximately 300 million Indonesian rupiah. According to this data, the amount of medical expenses has the potential to become an issue for the patient and the team of doctors in achieving optimal treatment, with the coverage from the National Health Insurance (Jaminan Kesehatan Nasional [JKN]) hopefully will reduce the economic burden on certain health issues, especially medical expenses in AAA cases that require an EVAR procedure.…”
Section: Discussionmentioning
confidence: 92%
“…Despite these, one major shortcoming associated with EVAR is the increased rate of graft-related complications leading to reintervention [6,7], with about 25-40% of patients needing re-intervention [8]. Thus, continuous postoperative surveillance and follow-up scans are warranted in EVAR patients, leading to increased costs [9][10][11][12][13]. Studies done in the UK found EVAR less cost-effective, with the conclusion that EVAR could only be a cost-effective use of NHS resources if fewer graft-related complications and reinterventions are observed [10].…”
Section: Introduction Backgroundmentioning
confidence: 99%